Effects of ketamine/xylazine and urethane anesthesia on compound muscle action potential latency of gastrocnemius muscle in rats - Beste Mentese; Hasan Fehmi Özel; Mustafa Özbek; Necip Kutlu (Neurological Sciences and Neurophysiology, 2023)
Objective: Anesthetic agents, which are used in appropriate doses for the application of the experimental procedure in animals, relieve pain when applied in sufficient amounts as well as muscle relaxation. However, many anesthetics can alter the dynamics of neuromuscular systems. We aimed to compare the effects of two frequently used anesthetic agents on electromyographic parameters in rats. Materials and Methods: This study was performed on male Wistar albino rats aged 22–24 months. The animals were divided into two groups: urethane (1.5 gkg−1, i.p; n = 6) and ketamine+xylazine (K+X) (80 mg/kg, i.p; n = 6). Under general anesthesia, rats were electrically stimulated with bipolar hook electrodes from both legs, and compound muscle action potential (CMAP) was recorded from the needle electrode of the gastrocnemius muscle. Motor nerve action potential latency (MNAPL) was measured from the sciatic nerve of the rats. Results: The results of electrodiagnostic findings related to two different anesthetics in the animals were compared, and CMAP parameters were found to differ between the groups. MNAPL in both the right and left legs was significantly reduced in the urethane group compared to the K+X group (P < 0.05). Conclusion: Urethane anesthesia may be a better choice than K+X anesthesia to evaluate nerve and muscle functions in animal electromyography studies.